Réponses

2013-04-17T19:46:33+02:00

1-5/6 = 6/6 - 5/6 = 1/6

1+1/6 = 6/6+1/6 = 7/6

7/9+(2-2*3)/(3-3*7) = 7/9 + (-4)/(-18) = 7/9 + 2/9 = 9/9 = 1

2013-04-17T20:15:03+02:00

bonjour .j'espere ne pas me tromper.

a)1-5          -4

      __       ___

       6           6        -4      2      -2     1       -2    3       -6

----------  = ----  =   __  : __ = __ :__  =  __x __  = __ = -2

1+ 1            2         6       6       3    3         3    1         3  

    __          __

    6              6

 

b)  7 + 2-2x3        7    2-6       7    -4        7     -2       

    __ +_____ =  __+___  = __+___ = __+___ = 5

     9   +3-3x7        9   3-21     9    -18      9     -9